Immediate Reconstruction of Massive Gluteal Defects Following Giant Malignant Peripheral Nerve Sheath Tumors Excision: Application of the Fasciocutaneous Rotational Flap in a Resource-Stratified Setting - Diah Mirlia; Haivan Kusuma Aji; Kiki Akhmad Rizki (HM Publisher, 2026)
Background: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive soft tissue sarcomas often requiring radical excision. In the gluteal region, achieving oncological clearance for giant tumors creates massive defects characterized by dead space and tension. This study evaluates the utility of the fasciocutaneous rotational flap for immediate closure when free tissue transfer is unavailable. Case presentation: A 56-year-old female presented with a rapidly enlarging, Grade III MPNST on the right buttock measuring 18 cm in diameter. Wide local excision resulted in a defect measuring 18 cm by 16 cm by 10 cm, exposing the gluteus maximus. Due to resource limitations preventing intraoperative frozen section analysis, wide anatomical clearance was prioritized. Immediate reconstruction was performed using a random-pattern fasciocutaneous rotational flap based on inferior gluteal artery perforators. The flap arc length measured 52 cm with a 1:3.25 defect-to-arc ratio. Postoperative histopathology confirmed Grade III MPNST with positive deep margins (R1), necessitating adjuvant radiotherapy. The flap healed completely by day 14 without necrosis, and the patient was discharged on day 5. At the 3-month follow-up, the wound remained stable with no dehiscence during radiation. Conclusion: The gluteal fasciocutaneous rotational flap is a robust technique for closing massive defects where primary closure is impossible. While it provides excellent durable coverage for adjuvant therapy, the inability to confirm negative margins intraoperatively poses significant oncological risks. Immediate flap coverage should be weighed carefully against staged reconstruction in resource-stratified settings.